Coaching of Futsal Sports Achievements in Clubs Ikatan Sarjana Olahraga Indonesia (ISORI) Medan, North Sumatera - Abdurrahman, Eka; Sulaiman, Sulaiman; Wira Yudha, Donny (Journal of Physical Education and Sports, 2020)
This study aims to evaluate antecedent, transactions, and outcomes at the ISORI Medan North Sumatra club. Antecedent (background and planning of coaching programs), transactions (recruitment of coaches, recruitment of athletes, training programs, facilities and infrastructure, funding, coordination, and welfare), outcomes (success / achievement). This research used a qualitative case study approach with the continuance evaluation model of Robert E. Stake. The subjects in this study were administrators, coaches, athletes, parents of athletes, and the surrounding community at the ISORI Medan North Sumatra club. The results of this study are the antecedent evaluation comprising the background and planning of the coaching program at the ISORI Medan North Sumatra club is clear and well structured, the evaluation of transactions comprising trainer and athlete recruitment has gone well, implementing the coaching program was good according to the program scheduled training, lack of facilities and infrastructure because there are still many that are not suitable for use, funding was not running well, it does not meet the needs of coaching, coordination had been running well, the welfare provided for coaches and athletes was not optimal, and evaluation of outcomes in the form of achievement athletes at the ISORI Medan North Sumatra club were not good enough because they were less stable to achieve in several events involved every year.